2018
DOI: 10.15640/jeds.v6n4a7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mobile Phone Ownership on Agricultural Productivity in Benin: The Case of Maize Farmers

Abstract: Given the importance of maize in the diet of citizens and country's objectives in terms of food security and export, a study on maize production is of great importance. This paper examines the effect of mobile phone ownership on agricultural productivity in Benin: The case of maize farmers. It uses a micro-data from Benin by adopting a two stages regression strategy. As previous studies, the results show significant evidence that mobile phone ownership improves maize farmers' productivity in Benin. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…When viewed from the difference between the amount of rice output of users and non-users of mobile phones for agricultural activities, the most significant difference is in the province of West Java. These findings follow the results of previous studies by Adenubi et al (2021); Aminou et al (2018);Feryanto & Rosiana (2021); Issahaku et al (2018); Khan et al (2022); Masuka et al (2016); Noubissi Domguia & Asongu (2022); Quandt et al (2020);and William et al (2021) which shows that ICT facilities in the form of cell phones significantly affect agricultural productivity.…”
Section: The Impact Of Using Cell Phones On Farmers' Productivity (Am...supporting
confidence: 91%
See 2 more Smart Citations
“…When viewed from the difference between the amount of rice output of users and non-users of mobile phones for agricultural activities, the most significant difference is in the province of West Java. These findings follow the results of previous studies by Adenubi et al (2021); Aminou et al (2018);Feryanto & Rosiana (2021); Issahaku et al (2018); Khan et al (2022); Masuka et al (2016); Noubissi Domguia & Asongu (2022); Quandt et al (2020);and William et al (2021) which shows that ICT facilities in the form of cell phones significantly affect agricultural productivity.…”
Section: The Impact Of Using Cell Phones On Farmers' Productivity (Am...supporting
confidence: 91%
“…Several previous studies have identified the determinants of using information and communication technology in the form of mobile phones by farmers. Several factors, including age, influence farmers' decisions to use mobile phones, length of education, income, marital status, home ownership status, and land area (Aminou et al, 2018;Folitse et al, 2019;Umaroh & Afifah, 2020;Feryanto & Rosiana, 2021;William et al, 2021). Folitse et al (2019), in their study using logistic regression analysis it was found that the coefficient of the age variable had a negative and significant relationship with the use of mobile phones as a communication tool for agricultural information.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using micro-level data, Aminou et al (2018) applied the Two-stage Least Squares (2SLS) and found that mobile phone ownership is statistically significant in explaining the level of agricultural productivity. According to the findings, access to a mobile phone by farmers, on average, can increase productivity by 0.13%.…”
Section: Ict and Youth In Agriculturementioning
confidence: 99%
“…Electronic dissemination of information (news, entertainment) to remote regions has drawn attention to alternative life experiences outside the rural realm and made migration to the city attractive to some. However, the same communication advances, notably the cell phone, have also enabled some agriculturalists to increase production and income, enhancing the security of rural livelihood (Aminou et al, 2018;Fabregas et al, 2019).…”
Section: Technological Dynamismmentioning
confidence: 99%